Integrating Ambidexterity into the Modern Manufacturing Era of Industry 4.0 - Elfindah Princes (International Journal of Supply Chain Management, 2020)
Ambidexterity has been a great solution for many problems so far especially in the world of industry. The swift and unpredictable changes in the market have pushed the industry to integrate ambidextrous capabilities in all aspects, in this case Modern Manufacturing process. Manufacturing talks about the Supply Chain Management from the beginning until the products reach the markets. There have been so many debates about how Ambidexterity will affect the Modern Manufacturing, if it creates burdens or instead it will give positive effects. The previous research has been contradictory between one another. Using systematic literature research and qualitative approach, this paper aims to analyze the needs of integrating ambidexterity into the Modern Manufacturing Era of Industry 4.0 to increase the competitive advantage for the company. The researcher concluded that despite all the debates, ambidexterity is a not an option for the future competitions, it is a must to solve disruptive problems due to technology advancement. There are important steps need to be taken in order to integrate ambidexterity capabilities into the company with clear deadlines and goals. We must also pay attention to the transition process in integrating ambidexterity in the manufacturing industry which may be different from other industries. The limitation of this research is there is no obvious and real example of successful manufacturing companies that have succeeded and taking detailed notes of the transition to further confirm the findings in this paper. Future research should address this.